Death, time and mortality in the later novels of Don DeLillo - Wolf, Philipp (New York, NY : Routledge, 2022)
This book offers the first systematic study of death in the later novels of Don DeLillo. It focuses on Underworld to The Silence, along with his 1984 novel White Noise, in which the fear of death dominates the protagonists most hauntingly. The study covers eight novels, which mark the development of one of the most philosophical and prestigious novelists writing in English. Death, in its close relation to time, temporality and transience, has been an ongoing subject or motif in Don DeLillo's oeuvre. His later work is shot through with the cultural and sociopsychological symptoms and responses death elicits. His "reflection on dying" revolves around defensive mechanisms and destruction fantasies, immortalism and cryonics, covert and overt surrogates, consumerism and media, and the mortification of the body. His characters give themselves to mourning andare afflicted with psychosis, depression and the looming of emptiness. Yet writing about death also means facing the ambiguity and failing representability of "death." The book considers DeLillo's use of language in which temporality and something like "death" may become manifest. It deals with the transfiguration of time and death into art, with apocalypse as a central and recurring subject, and, as a kind of antithesis, epiphany. The study eventually proposes some reflections on the meaning of death in an age fully contingent on media and technology and dominated by financial capitalism and consumerism. Despite all the distractions, death remains a sinister presence, which has beset the minds not only of DeLillo's protagonists.
Keywords: DeLillo, Don -- Criticism and interpretation; Death in literature; LITERARY CRITICISM / American / General; SOCIAL SCIENCE / Death & Dying